Determinants of ex-combatants' attitudes toward transitional justice in Colombia. (November 2018) - Daly, Sarah Zukerman
This article draws on original survey data of 10, 951 Colombian ex-paramilitaries to study the determinants of victimizers' support for transitional justice. Understanding ex-combatants' attitudes toward victims of the conflict and measures of justice is critical to gaining leverage on when transitional justice is likely to prove effective. The data suggest that former fighters' views of transitional justice are shaped by the intimacy with which they experience transitional justice: whether they are known to, in close proximity, and accepted by the communities they victimized. Their attitudes are also constrained by the norms of justice in which they have been socialized, and by the extent of the risks to them personally: in judicial terms given their own culpability and in security terms given their vulnerability to retribution. The study has important implications for the prospects of successful transitional justice with the FARC rebels and for the consolidation of peace in Colombia.